Riluzole prevents oxaliplatin-induced cold allodynia via inhibition of overexpression of transient receptor potential melastatin 8 in rats - Shota Yamamoto; Nobuaki Egashira; Makoto Tsuda; Satohiro Masuda (Elsevier, 2018)
Oxaliplatin causes acute cold hypersensitivity in most patients. We previously reported oxalate derived from oxaliplatin induced cold allodynia via overexpression of transient receptor potential melastatin 8 (TRPM8) in the dorsal root ganglion (DRG) in rats. In this study, we examined the effect of riluzole on oxaliplatin-induced cold allodynia. In cultured DRG neurons, riluzole suppressed oxalate-induced increase of the number of menthol (TRPM8 agonist)-sensitive cells. Moreover, riluzole prevented cold allodynia and increase in levels of TRPM8 mRNA in oxaliplatin-treated rats. These results suggest that riluzole prevents oxaliplatin-induced cold allodynia via inhibition of TRPM8 overexpression in the DRG. Keywords: Oxaliplatin-induced cold allodynia, Riluzole, TRPM8